PENGARUH ROA, ROE, CAR, NPL, INFLASI DAN KURS TERHADAP BOPO PADA BANK UMUM SYARIAH DI INDONESIA TAHUN 2008 – 2015 - B2051132013, IRWANTO (Jurnal Ekonomi Daerah (JEDA), 2018)
This study aims to determine how the effect of variable ROA, ROE, CAR, NPL, inflation, and exchange rate against BOPO the player in global Islamic Bank, where ROA is the ratio to measure the efficiency of the Bank.            This study uses multiple regression analysis in which the data used are quarterly time series data as much as 32 (2008 quarter 1-2015 4th quarter), where secondary data downloaded through the BI and CPM, then processed using the help eviews 9.            The results showed independent variables affect the dependent variable then proceeds Return Of assets (ROA) explains that the profit of the Bank syariah high makes Efficiency Banking is getting better, while the Return Of Equity (ROE) explains the contrary, because of high taxes so the profit after tax low compared with the total capital of the islamic bank and then the bank has a capital adequacy Ratio (CAR) or higher capital adequacy of less efficient because it avoids the risk and manage the funds safer and lower in the portfolio. Meanwhile, non-performing loans (NPL) indeed leads to efficiency Islamic Bank declined since the Bank became burdened by customers who do not pay the loan, the inflation and the exchange rate (exchange rate) increases causing the efficiency of Islamic banking increased driven by people's desire to increase revenue so that communities can deposit their funds into islamic banks in the form of savings or investments (mudaraba muthlaqah) and islamic banks will use the funds into financing activitiesKeywords: BOPO, ROA, ROE, CAR, NPLs, Inflation And Exchange